The Effect of Role-Play Method In English Speaking Skill - Akmal Akmal (Smart Education, 2018)
This study is focused on the speaking skill of M.Ts. Muhammadiyah students on grade VIII because the writer saw that their speaking skill is still so low. Role-Play is a classroom activity which gives the students the opportunity to practice the language. In this study, the writer used the experimental research design which it needs the pre-test and post-test to know their progress in speaking. In experimental, there are control class (conventional class) and experimental class. The writer have to make the treatment for experimental class so that it can be seen their progress after doing the treatment before taking the post-test. In findings data, the writer has got the score of control and experimental classes’ pre-test; the control class average score is 60 and the experimental class is 63, 47. The post-test score average, control class is 65,21 and experimental class is 81,73. In pre-test, the lowest score either in control class or experimental class is 50 and the highest is 80. In post-test, the lowest score is still 50 and the highest score is still 80 , but in experimental, the lowest score is 70 and the highest score is 90. The value of the t-test is 5.41 and it means that 5,41 > 2.66. Finally, the t-test is higher than t-table for both the significance level. (5.41>2.00 and 5.41>2.66). Keywords: speaking skill, role-play, control class, experimental class, treatment